The Relationship between Self-Adjustment and Self-Esteem with Self-Disclosure in Adolescents - Nur’Aeni Nur’Aeni; Liza Rizqi Ambarwati (Proceedings Series on Social Sciences & Humanities, 2021)
This study examines the relationship between self-adjustment and self-esteem with self-disclosure in adolescents at SMP N 3 Pangkah. Self-disclosure is the use of communication that is needed to make it easier for teenagers to adapt to the surrounding environment and adapt well in society and judge themselves from the views of other individuals. This study uses the Self Disclosure Scale (40 items), Self-Adjustment Scale (40 items), and Self-Esteem Scale (40 items). The population in this study were 7th-grade students of SMP Negeri 3 Pangkah located in Grobog Kulon, Pangkah District, Tegal Regency, Central Java Province, Indonesia, which consisted of 8 classes with a total of 256 students. While the sample in this study consisted of 4 types of 100 students of class VII, SMP Negeri 3 Pangkah was obtained using simple random sampling.The self-disclosure scale has a reliability of 0.907, a self-adjustment scale of 0.796, a self-esteem scale of 0.839. With the results of Cronbach's alpha value close to 1.00, it can be used for research.The proposed hypothesis results are accepted based on the study results obtained R= 0.901 with p = 0.000 (p <0.05). There is a significant relationship between Self Disclosure with Self-Adjustment and Self-Esteem in 7th-grade students at SMP Negeri 3 Pangkah. The correlation results show a positive value indicating that the higher the self-adjustment and self-esteem, the higher the self-disclosure.